ANALISIS LITERATUR SISTEMATIS TENTANG PENGGUNAAN BUKU CERITA FABEL BERBASIS MULTIMODE UNTUK MENINGKATKAN KETERAMPILAN MEMBACA KREATIF TEKS FABEL PADA SISWA SEKOLAH DASAR - Zhian Nurajijah; Dudu Suhandi Saputra; Indani Damayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Creative reading skills are essential in Indonesian language learning at the elementary school level as they involve students’ abilities to comprehend, interpret, and develop ideas based on texts. This study aims to analyze research trends and the effectiveness of using multimodal fable storybooks in improving students’ creative reading skills of fable texts in elementary schools. This study employed a Systematic Literature Review (SLR) method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines through the stages of identification, screening, eligibility, and inclusion. Literature searches were conducted using Google Scholar and Scopus databases, resulting in 15 selected articles for further analysis. The findings reveal that previous studies were predominantly conducted using the Research and Development (R&D) method with 4D and ADDIE development models. The developed media included flipbooks, digital books, e-books, and pop-up books that integrated text, images, audio, and interactive elements. The synthesis results indicate that multimodal fable storybooks effectively support students’ creative reading skills by improving text comprehension, reading engagement, interpretation, and creative responses toward stories.